Microstructure and Mechanical Properties of Twin-Roll Strip-Cast Al-5.5Mg-0.02Ti Alloy Sheet - Cheon, Boo-Hyeon; Han, Jun-Hyun; Kim, Hyoung-Wook; Lee, Jae-Chul (KOREAN INST METALS MATERIALS, 2010)
High-strength aluminum alloy sheets with high magnesium contents were fabricated by a strip caster equipped with an asymmetric nozzle, which has been proven to be effective for reducing surface defects and internal segregation. 4 mm thick as-cast sheets consisting of fine dendrites and minor Al8Mg5 segregation were hot-rolled successfully to 1 mm sheets and subsequently annealed at various temperatures. The sheet revealed the tensile strength and elongation of 306 MPa and 34%, respectively, when it was rolled at 250 degrees C and subsequently annealed at 475 degrees C, which exhibits the feasibility of the practical application for autobodies. The observed mechanical properties were explained on the basis of the microstructural characteristics of the alloy sheets.
Keywords: AL-MG ALLOY; BIMODAL GRAIN-SIZE; LE-CHATELIER BANDS; TENSILE DUCTILITY; ALUMINUM-ALLOY; HIGH-STRENGTH; DEFORMATION; SIMULATION; STEELS